Antiphospholipid antibodies predict imminent vascular events independently from other risk factors in a prospective cohort - Neville, Carolyn; Rauch, Joyce; Kassis, Jeannine; Solymoss, Susan; Joseph, Lawrence; Belisle, Patrick; Levine, Jerrold M.; Fortin, Paul R. (Thrombosis and Haemostasis, 2009)
Antiphospholipid antibodies (aPL) are associated with vascular events, but the magnitude of this risk, alone, or in combination with other atherogenic and thrombophilic risk factors, remains unclear. A prospective cohort of 415 persons was studied for arterial and venous events (AE and VE) over a median time of 7.4 years. aPL and coagulation abnormalities were measured upon beginning of the study and annually for the first four years. Within the cohort, a nested case-control study was conducted to investigate the role of endothelial and inflammatory markers in predicting new vascular events. Forty-five individuals had new vascular events: 18 occurred during the first year of follow-up. The proportion of event-free survivors at eight years was 90% (95%CI = 87%, 94%) for aPL-negative and 72% (60%, 85%) for aPL-positive individuals, respectively. Predictors for new AE were previous AE (HR=5.7 [2.7, 12.0]), diabetes (5.6 [2.4, 13.2]), aPL positivity (2.6 ([1.2, 5.9]), and age (1.04 [1.01, 1.07]). New VE were predicted by previous VE (6.1 [1.9, 19.9]), anti-β2-glyco-protein I (aβ2GPI) positivity (5.8 [1.4, 24.1]), activated protein C resistance (APCR) (4.1 [1.1, 15.1]), and gender (3.7 [1.1, 12.9]). In the nested case-control study, similar predictors were observed for AE, while abnormal APCR (OR=5.5 [1.1, 26.6]) and elevated von Willebrand factor (vWF) (OR=5.0 [1.2, 19.8]) best predicted VE. We demonstrate that aPL independently predict new vascular events and discriminate between individuals with and without events in the first two years of follow-up, indicating that aPL are associated with a short-term risk of developing new and recurrent vascular events.
Keywords: Antiphospholipid antibodies; thrombosis; anti-beta2-glycoprotein I; activated protein C resistance; von Willebrand factor